2022
DOI: 10.4274/balkanmedj.galenos.2022.2022-6-16
|View full text |Cite
|
Sign up to set email alerts
|

COL3A1 Overexpression Associates with Poor Prognosis and Cisplatin Resistance in Lung Cancer

Abstract: Background: Collagen type III alpha 1 chain (COL3A1) is reported to mediate drug resistance in various cancers, and public database analysis indicated its overexpression in lung cancer. Aims: To investigate the effects of COL3A1 on modulating cisplatin (DDP) resistance in lung carcinoma. Study Design: A cell study. Methods: Gene Expression Omnibus datasets were used to determine the differentially expressed genes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Additionally, we performed gene-set enrichment analysis on the identified DE genes with MSigDB gene-sets 13, 14 , identifying significantly down-regulated pathways that are relevant to collagen, such as collagen-activated tyrosine kinase receptor signaling pathway and collagen metabolic and catabolic process (Figure 4E). Previous studies have found that the overexpression of collagen genes such as COL11A1 15 and COL3A1 16 in NSCLC may indicate poor prognosis and drug resistance, and COL1A1 is correlated with immune infiltration in NSCLC 17 . Our finding of these genes that are expressed significantly more in the tumor cells from the macrophage neighborhood than tumor cells from the stromal neighborhood can potentially lead a more detailed investigation of the biological mechanism about transcriptional changes within the context of cancer spatial TME studies.…”
Section: Resultsmentioning
confidence: 97%
“…Additionally, we performed gene-set enrichment analysis on the identified DE genes with MSigDB gene-sets 13, 14 , identifying significantly down-regulated pathways that are relevant to collagen, such as collagen-activated tyrosine kinase receptor signaling pathway and collagen metabolic and catabolic process (Figure 4E). Previous studies have found that the overexpression of collagen genes such as COL11A1 15 and COL3A1 16 in NSCLC may indicate poor prognosis and drug resistance, and COL1A1 is correlated with immune infiltration in NSCLC 17 . Our finding of these genes that are expressed significantly more in the tumor cells from the macrophage neighborhood than tumor cells from the stromal neighborhood can potentially lead a more detailed investigation of the biological mechanism about transcriptional changes within the context of cancer spatial TME studies.…”
Section: Resultsmentioning
confidence: 97%
“… 23 A series of studies have cataloged the implication of deregulated proteins in drug resistance of NSCLC. 24 , 25 Previous work unveils the important role of COL3A1 in DDP resistance development of NSCLC, 15 but its regulatory factors are not fully understood. In this work, we focused on COL3A1 and found that COL3A1 expression is enhanced in DDP-resistant NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…To study the effect on DDP resistance, we also procured A549 cells with DDP resistance (A549/DDP, #CL-0519) from Procell. The H460/DDP cell line derived from H460 cell line was generated and maintained as described by Wang and colleagues 15 using DDP reagent (Selleck, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…COL3A1 overexpression has been discovered in multiple cancer cell types, including breast, ovarian, and colorectal cancer. 37 , 38 …”
Section: Discussionmentioning
confidence: 99%